O efeito China na competitividade internacional da indústria brasileira: uma análise pela complementaridade de comércio dos países parceiros - Steffen, Nadine Führ (Universidade do Vale do Rio dos Sinos, 2022)
Over the last decades, there have been significant ongoing transformations in the profile and dimension of relations between countries. The prevailing theoretical concepts are challenged, and new contributions are presented based on empirical ob-servation, thus giving more emphasis to the role of demand in the productive and com-mercial configuration, as well as a determinant of the competitive position of industries and countries worldwide. In this context, the virtuous expansion performed by China stands out, through significant growth rates in foreign trade and industrial production. As argued by Módulo and Hiratuka (2017), China's dynamism in exports of industrial-ized products creates challenges and opportunities for other countries, especially those seeking to maintain a relevant industrial structure. Among the challenges, the competition of the country's exports with Chinese exports in third markets stands out. The objective of the present work is based on this, which is to measure the effect of the competitiveness of Chinese exports of industrialized products on the competitive-ness of Brazilian exports of the same products. To reach the objective, an interaction indicator between China's market share in Brazil's partner country and the comple-mentarity of trade of the same country with China and the United States was built. As a general hypothesis, it is suggested that the effect of China on Brazil's competitive-ness may vary according to the trade complementarity of the partner country, with a greater effect expected when trade complementarity is greater with China than with the United States. Only industrialized products are treated, and 35 countries are part of the sample, observed from 2000 to 2019. As methodology, panel data models are proposed with application of the instrumental variables estimator from the Generalized Method of Moments (IV-GMM). The results validate the hypothesis when the partner's trade complementarity with China is higher, evidencing the occurrence of competitive effects of China on Brazil, in the sense of loss of market share in industrialized products in third markets.
Keywords: Brasil; China; Competitividade; Complementaridade de comércio; Método generalizado dos momentos; Brazil; Competitiveness; Trade complementarity; Generalized method of moments; ACCNPQ::Ciências Sociais Aplicadas::Economia